Knowledge management and job performance in the public sector - Mustapa, Azrain Nasyrah; Mahmood, Rosli (2016)
The growing of consciousness about public sector service effectiveness and efficiency are important issues among many countries including Malaysia. The publics have risen up concerns due to the current level of service condition and routine performance.Majority of the complaints points out about delays in service provision, unfair action/decision on part of administration, abuse of power and failure to enforce rules. Public sector service provider should alert the issues because communities are more educated than before, whereby they could compare the systems from other countries around the world. Due to the interest of addressing the practical and theoretical issues and proposing the understanding on factors which will influence job performance among public servants in local governments, the study intends to examine the role of public service motivation (PSM) as a mediator of knowledge management and job performance relationship. This study involved officers among the Management and Professional Group (MPG) (grade 41-54) from Malaysian Local Governments.Questionnaires have been distributed to the middle managers of 149 Malaysian Local Governments representing 3 main categories; City Hall/ City Council, Municipal Council and District Council. This study used the partial least squares (PLS) and structural equation modeling (SEM) tools to examine factors influencing job performance. Statistical results confirm that knowledge management has an impact on job performance. Public service motivation also mediates the association between knowledge management and job performance. Findings will help management within local governments to provide best practices to employees and society.Limitations and suggestions for future research are also provided.